Formation of New Attitudes Towards Social Justice Under Globalization - Teshaboev Mukhiddin Marifovich (Periodica Journal, 2023)
In this article, the most common trend in globalization is the strengthening of regionalism, which forms an independent territorial and socio-cultural society under the influence of general historical, spatial-geographical and ethnic-cultural conditions and others. Observing the continuous evolution of "social justice" from ancient history helps us define the concept and place of social justice.
Keywords: sphere; democracy; globalization